Response to Tcherkez and Farquhar Rubisco adaptation is more limited by phylogenetic constraint than by catalytic trade-off - Bouvier, Jacques W (Journal of plant physiology, 2023)
Copyright © 2023 Elsevier GmbH. All rights reserved.